Chronic adnexal torsion: An under-recognized disease entity. (March 2017) - Takeda, Akihiro; Hayashi, Shotaro; Teranishi, Yoshie; Imoto, Sanae; Nakamura, Hiromi
Abstract: Objective: To clarify the incidence, clinical background and surgical characteristics of chronic adnexal torsion in comparison to acute adnexal torsion. Study design: The patients were divided into three categories based on the period from the onset of symptoms to surgical management: acute (≤24 h), subacute (2 days) and chronic adnexal torsions (≥3 days). Cases, in which the onset of symptoms was unspecified, were included in the chronic adnexal torsion group. Then, a retrospective comparative study of acute (49 patients) and chronic adnexal torsion (45 patients) was performed. Laparoscopic surgery was performed as a primary surgical procedure. Results: In chronic adnexal torsion, surgery was performed at a median of 9 days (range: 3–270 days) after the onset of symptoms. The apparent onset of symptoms was not noted in 2 cases. All cases with acute adnexal torsion received emergency surgery. In contrast, emergency surgery was performed only in 13 patients with chronic adnexal torsion. Patients with chronic adnexal torsion were significantly older than those with acute adnexal torsion. Isolated tubal torsion was more frequent in chronic adnexal torsion. With the exception of 2 cases with chronic adnexal torsion in which laparotomic conversion was required due to severe adhesion, and 2 cases with acute adnexal torsion with advanced gestational age, who were managed by initial laparotomy, laparoscopic surgery was successful. Unilateral salpingo-oophorectomy was the most frequent surgical procedure in both groups. When confined to the patients who expressed a wish for adnexal preservation, adnexal cystectomy or detorsion was possible in 60.9% of the acute torsion cases and 57.1% of the chronic adnexal torsion cases. Severe necrosis of the adnexal tissue and extensive pelvic adhesion were the more frequent associated conditions in chronic adnexal torsion. Among the patients who were successfully managed by laparoscopic surgery, the duration of surgery was significantly longer in the patients with chronic adnexal torsion. Severe necrosis that makes a pathological diagnosis difficult was the most frequent finding in cases of chronic adnexal torsion. Conclusion: Chronic adnexal torsion still represents a diagnostic and therapeutic challenge that should be recognized as a distinct and more frequently encountered disease entity.